ALTERNATIVE LEVOTHYROXINE ADMINISTRATION VIA THE RECTAL ROUTE: A CASE REPORT - Sorsona, Francis; Uy-Ho, Jean (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Hypothyroidism is commonly replaced with oral levothyroxine, however, there are cases wherein the oral route may not be available or contraindicated, and parenteral preparations are not accessible. We report an alternative way of administering levothyroxine in a 70-year-old Filipino male diagnosed with post-surgical hypothyroidism. The accidental removal of the nasogastric tube served as a dilemma on how to continue levothyroxine replacement prior to gastrostomy tube insertion. With no definite guidelines, levothyroxine was prepared in a saline solution in increasing dosage via rectal enema. Serial-free T4 and T3 were measured until normalization just prior to surgery. High doses of levothyroxine enema proved as an alternative and effective way of managing hypothyroidism when the conventional route is contraindicated and parenteral preparations are not available. This case report however does not recommend rectal administration over the oral route, but this can be a useful guide for future cases that may require levothyroxine administration via the rectal route.